2020
DOI: 10.1089/ast.2018.1908
|View full text |Cite
|
Sign up to set email alerts
|

First Detections of Dichlorobenzene Isomers and Trichloromethylpropane from Organic Matter Indigenous to Mars Mudstone in Gale Crater, Mars: Results from the Sample Analysis at Mars Instrument Onboard the Curiosity Rover

Abstract: Chromatographic analysis of the Cumberland mudstone in Gale crater by the Sample Analysis at Mars (SAM) instrument revealed the detection of two to three isomers of dichlorobenzene. Their individual concentrations were estimated to be in the 0.5-17 ppbw range relative to the sample mass. We also report the first detection of trichloromethylpropane and the confirmation of the detection of chlorobenzene previously reported. Supporting laboratory experiments excluded the SAM internal background as the source of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 57 publications
(68 reference statements)
2
47
0
Order By: Relevance
“…ancient life (Eigenbrode et al 2018). These findings are consistent with those obtained from ALH 84001 (Thomas-Keprta et al 2009), the detection of chlorobenzeen and dischloroalkanes previously found in Gale Crater mudstone (Freissinet et al 2015), the chloromethanes detected during the 1976 Viking mission (Navarro-González et al 2010), and other indices of organics (Szopa et al 2020;Wright et al 1989). Organic matter not only provides an energy source and supports microbial carbon recycling, but represents the biological activity and residue of past life.…”
Section: Soil -Atmosphere Exchange and Abiogenic Oxygen?supporting
confidence: 84%
“…ancient life (Eigenbrode et al 2018). These findings are consistent with those obtained from ALH 84001 (Thomas-Keprta et al 2009), the detection of chlorobenzeen and dischloroalkanes previously found in Gale Crater mudstone (Freissinet et al 2015), the chloromethanes detected during the 1976 Viking mission (Navarro-González et al 2010), and other indices of organics (Szopa et al 2020;Wright et al 1989). Organic matter not only provides an energy source and supports microbial carbon recycling, but represents the biological activity and residue of past life.…”
Section: Soil -Atmosphere Exchange and Abiogenic Oxygen?supporting
confidence: 84%
“…About 30 years later, the Phoenix lander reported the widespread presence of perchlorates (Hecht et al, 2009), leading Navarro-González et al (2010) to suggest that the Cl-rich compounds detected by the Viking landers were produced by reactions of martian organic materials with perchlorates during the pyrolytic measurements. This view has since been supported by laboratory experiments (Steininger et al, 2012;Glavin et al, 2013;Miller et al, 2015;François et al, 2016;Guzman et al, 2018) and confirmed by the detection of Cl-rich organics by Sample Analysis at Mars (SAM), the pyrolysis GCMS on board Curiosity (Leshin et al, 2013;Ming et al, 2014;Freissinet et al, 2015;Eigenbrode et al, 2018;Szopa et al, 2020). In addition, diverse pyrolysis products, including S-rich organics, were recently detected by SAM (Eigenbrode et al, 2018), confirming the presence of organic compounds in the subsurface of Mars.…”
Section: Introductionmentioning
confidence: 72%
“…However, the amount of oxidation that occurs, and products formed, will depend on the chemistry and packaging of organic materials and the oxychlorine phases in a sample. In some cases organic material survives oxidation during thermal analyses as demonstrated by SAM's detection of organic compounds in samples also containing perchlorates [93][94][95]. In particular, aromatic, aliphatic, and thiophenic products evolve at temperatures higher than oxychlorine O 2 releases [94].…”
Section: Implications For Gale Crater Samplesmentioning
confidence: 99%